Eating behaviours and associated lifestyle factors in a sample of Slovak adolescents - Vondrová, Diana; Argalášová, Ľubica; Weitzman, Michael; Samohýl, Martin; Filová, Alexandra; Hirošová, Katarína; Jurkovičová, Jana; Rimárová, Kvetoslava; Dorko, Erik; Babjaková, Jana (Central European journal of public health, 2024)
OBJECTIVES: An unhealthy lifestyle, inappropriate eating habits, and inadequate physical activity are the most common risk factors affecting health and causing the premature onset of non-communicable diseases. The study aimed to evaluate lifestyle factors, eating habits, and daily regimens in a sample of Slovak adolescents. METHODS: The sample involves 524 students aged 15-22 years attending selected secondary schools from the model region of Bratislava, the capital of Slovakia. We assessed the prevalence of selected lifestyle factors and investigated the relationship between negative lifestyle factors and the presence of overweight and obesity. RESULTS: We found eating irregularities including avoidance of school lunch, inadequate daily consumption of vegetables, dairy products and wholegrain foods, and the high consumption of sweets and sweetened beverages. The prevalence of excess weight and obesity in the sample was 18.4%. Compared to the non-obese, overweight or obese students had significantly lower daily consumption of vegetables and used to avoid sports more frequently. Almost 37% of students did not do sports at all. Students who were not doing sports on regular basis used to skip breakfast more frequently, they ate fewer vegetables and more sweets and spent considerable time in sedentary activities. CONCLUSION: In the sample of secondary school students, we investigated several negative lifestyle factors and the relatively high prevalence of overweight and obesity. The results of the study can be used for the development of preventive measures to protect and promote the health of children and youth.
Keywords: Young Adult; Sedentary Behavior; stravovací zvyklosti; studenti; Male; Overweight; Slovakia; obesity; Obesity; Slovenská republika; Risk Factors; mladý dospělý; overweight; Adolescent; obezita; prevalence; Life Style; mužské pohlaví; nadváha; adolescents; mladiství; životní styl; lidé; sedavý životní styl; ženské pohlaví; Students; Humans; daily activities; rizikové faktory; Prevalence; eating habits; Female; Feeding Behavior